Nursing Care for Patient Mr. W Post-op Hemorrhoidectomy in the Kemuning Ward of Waled Regional General Hospital in Cirebon Regency - Putri Shintia Devi; Dewi Erna Marisa; Nosa Amelinda W; Abdul Rouf (Al Makki Publisher, 2024)
Haemorrhoids or better known as piles or haemorrhoids are the discharge of flesh from the anus (rectum) due to complex and repeated bowel movements and are often accompanied by blood due to injury. Hemorrhoids are a dangerous disease that can interfere with daily activities, decreasing a person's quality of life. Hemorrhoidectomy is a surgical process to remove haemorrhoids. This study aims to carry out nursing care actions on clients with post-op hemorrhoidectomy. The research method used is a descriptive method with a case study approach. The results of this study include the assessment, diagnosis, intervention, implementation and evaluation. After nursing care was provided to Mr. W's client, the nursing problems were resolved. W obtained the results of resolved and unresolved nursing problems. The patient said the pain was reduced, he did not grimace, and he looked calm; the patient said he was afraid of defecation due to post-op wounds and hard faeces, and the client was allowed to go home. Application of nursing care to clients with post-op hemorrhoidectomy in Mr. W's client between theory and case. W between theory and case. This can be proven in the application of theory to clients. This research aims to increase understanding and practice of nursing care in post-hemorrhoidectomy patients to achieve more optimal results.